Wavelength Tuning Free Transceiver Module in OLT Downstream Multicasting 4λ × 10 Gb/s TWDM-PON System - M. S. Salleh; A. S. M. Supa’at; S. M. Idrus; S. Yaakob; Z. M. Yusof (Journal of Computer Networks and Communications)
We propose a new architecture of dynamic time-wavelength division multiplexing-passive optical network (TWDM-PON) system that employs integrated all-optical packet routing (AOPR) module using 4λ×10 Gbps downstream signal to support 20 km fiber transmission. This module has been designed to support high speed L2 aggregation and routing in the physical layer PON system by using multicasting cross-gain modulation (XGM) to route packet from any PON port to multiple PON links. Meanwhile, the fixed wavelength optical line terminal (OLT) transmitter with wavelength tuning free features has been designed to integrate with the semiconductor optical amplifier (SOA) and passive arrayed waveguide grating (AWG). By implementing hybrid multicasting and multiplexing, the system has been able to support a PON system with full flexibility function for managing highly efficient dynamic bandwidth allocation to support the 4λ×10 Gb/s TWDM-PON system used to connect 4 different PON links using fixed wavelength OLT transceivers with maximum 38 dB link loss.